2008
DOI: 10.1007/s00221-008-1636-x
|View full text |Cite
|
Sign up to set email alerts
|

Soleus H-reflex modulation during body weight support treadmill walking in spinal cord intact and injured subjects

Abstract: The soleus H-reflex modulation pattern was investigated in ten spinal cord intact subjects during treadmill walking at varying levels of body weight support (BWS), and nine spinal cord injured (SCI) subjects at a BWS level that promoted the best stepping pattern. The soleus H-reflex was elicited by tibial nerve stimulation with a single 1-ms pulse at an intensity that the M-waves ranged from 4 to 8% of the maximal M-wave (M(max)). During treadmill walking, the H-reflex was elicited every four steps, and stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 71 publications
4
62
0
Order By: Relevance
“…With the subject standing at a BWS similar to that utilized during stepping, the stimulation sites were reevaluated, and the MG and/or TA M-wave MT was reestablished. Then, 80 to 130 stimuli were delivered at 0.2 Hz to assemble the soleus M-wave and H-reflex recruitment curves (Knikou et al 2009Smith et al 2015).…”
Section: Reciprocal and Ib Inhibition During Assisted Steppingmentioning
confidence: 99%
See 2 more Smart Citations
“…With the subject standing at a BWS similar to that utilized during stepping, the stimulation sites were reevaluated, and the MG and/or TA M-wave MT was reestablished. Then, 80 to 130 stimuli were delivered at 0.2 Hz to assemble the soleus M-wave and H-reflex recruitment curves (Knikou et al 2009Smith et al 2015).…”
Section: Reciprocal and Ib Inhibition During Assisted Steppingmentioning
confidence: 99%
“…The knee joint during the swing phase moves the stimulating electrode away from the tibial nerve, while knee extension during the stance phase has the opposite effect. To counteract these confounding factors, a supramaximal stimulus to the tibial nerve was delivered at 60 ms after the unconditioned or the conditioned H reflex at each bin of the step cycle (Knikou et al 2009Mummidisetty 2011, 2014). The customized LabVIEW software measured the peak-to-peak amplitude of the M wave and M max recorded during stepping and used a self-teaching algorithm to adjust the stimulus intensity at each bin of the step cycle.…”
Section: Reciprocal and Ib Inhibition During Assisted Steppingmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy subjects, the H reflex amplitude modulation by TMS shows an early phase, peaking at 10-30 ms, and a late phase, peaking at 60-130 ms. [12][13][14] According to Valls-Solé and co-workers, 13 the first phase may result from the generation of an excitatory postsynaptic potential (EPSP) in the a-motoneuron, whereas the mechanisms responsible for the second phase are not clear. In a study of patients with SCI, Wolfe et al 17 reported the absence of modulation in patients with complete motor lesions, and a partial facilitation present on incomplete motor lesions (ASIA C and D).…”
Section: Discussionmentioning
confidence: 99%
“…These intervals were chosen in view of their relevance for definition of the pattern of TMS modulation of the H reflex. 12,14 We collected five responses at each interval. The intertrial interval was at least 10 s to prevent carryover effects.…”
Section: Methodsmentioning
confidence: 99%